STORYTELLING WITH THE ASSURE MODEL AND CONTENT-BASED APPROACHES TO IMPROVE 3RD-6TH GRADE STUDENT'S SPEAKING SKILLS AT SIKKOLA RAKYAT - Lusy Sitanggang; Juliana Sidauruk; Evelyn Zebua; Faiz Nasution; Meisuri Ginting (Adisam Publisher, 2025)
This research explores the integration of the ASSURE Model and content-based approaches to enhance the speaking skills of 3rd–6th grade students at Sikkola Rakyat. Speaking prof iciency is a crucial aspect of language learning, yet many young learners struggle with confidence, fluency, and engagement in English communication. The ASSURE Model provides a systematic framework for lesson planning, ensuring that instructional strategies are tailored to students' needs. Meanwhile, the content-based approach immerses learners in meaningful and contextually rich materials, fostering natural language acquisition. Using a qualitative research design, this study examines the effectiveness of these combined methods through classroom observations and student performance assessments. The findings reveal that implementing the ASSURE Model alongside content-based learning significantly improves students' speaking abilities, participation, and overall language confidence. This study underscores the importance of structured and interactive teaching methods in developing young learners' communication skills.